2018
DOI: 10.1080/07391102.2018.1517610
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in silico study of the differences in the structure and ligand interaction properties of three alpha-expansin proteins from Fragaria chiloensis fruit

Abstract: Expansins are cell wall proteins associated with several processes, including changes in the cell wall during ripening of fruit, which matches softening of the fruit. We have previously reported an increase in expression of specific expansins transcripts during softening of Fragaria chiloensis fruit. Here, we characterized three α-expansins. Their full-length sequences were obtained, and through qRT-PCR (real-time PCR) analyses, their transcript accumulation during softening of F. chiloensis fruit was confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 67 publications
2
11
1
1
Order By: Relevance
“…Thus, high diversity was found in the first and last 25 positions of the N-terminus and C-terminus respectively, except for AtEXPA24. In addition, both AnEXPA1 and AnEXPA2 had two domains; the first one (DPBB_1) had between 60 and 145 amino acids (Figure 1 domain I), and the second (Pollen_allerg_1, CBM63) domain ranged from amino acids 158 to 229 (Figure 1 domain II) [25]. The signal peptide of AnEXPA1 was from one to 22 amino acids long, with a cleavage site between 22 and 23 amino acids, but that of AnEXPA2 was from one to 18 amino acids long, with a cleavage site between 18 and 19 amino acids (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, high diversity was found in the first and last 25 positions of the N-terminus and C-terminus respectively, except for AtEXPA24. In addition, both AnEXPA1 and AnEXPA2 had two domains; the first one (DPBB_1) had between 60 and 145 amino acids (Figure 1 domain I), and the second (Pollen_allerg_1, CBM63) domain ranged from amino acids 158 to 229 (Figure 1 domain II) [25]. The signal peptide of AnEXPA1 was from one to 22 amino acids long, with a cleavage site between 22 and 23 amino acids, but that of AnEXPA2 was from one to 18 amino acids long, with a cleavage site between 18 and 19 amino acids (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…In the CBM63 domain, the different amino acids of AnEXPA1 (A) and AnEXPA2 (V) were located in the 183rd position, whereas S (AnEXPA1) and P (AnEXPA2) were at the 194th position. Therefore, the different amino acids of these two genes could lead to differences in their protein structure and function [25,27,28].…”
Section: Resultsmentioning
confidence: 99%
“…In F. chiloensis fruit five expansins have been analyzed and the expression level of FcEXP1 , FcEXP2 and FcEXP5 correlates with fruit firmness reduction (Figueroa et al, 2009). The participation of these three gene isoforms suggests functional redundancy, however, a recent bioinformatics approach analyzed the interaction of each of these expansins with different cell wall polysaccharides (Valenzuela-Riffo et al, 2018). The results suggest that expansin proteins can bind not only cellulose but also other cell wall polymers such as xyloglucans of different conformation.…”
Section: Metabolism Of Other Cell Wall Polysaccharidesmentioning
confidence: 99%
“…On the other hand, the Chilean strawberry fruit (Fragaria chiloensis) has been described as a fruit with excellent organoleptic properties, highlighting its aroma and flavor [35]; however, the Chilean strawberry fruit has a high softening rate [35][36][37][38]. It was reported that total cell wall material decreases during fruit ripening, coincident with the loss of firmness [35,36].…”
Section: Introductionmentioning
confidence: 99%